Factors predicting menstrual irregularity among university students in Ho Chi Minh City, Vietnam: A cross-sectional study - Nguyen, Nhan Thi; Le, Trinh Thi My (Belitung Raya Foundation, Indonesia, 2024)
Background: University students often face menstrual irregularities, particularly among healthcare students, due to rigorous study environments, such as night duties resembling professional staff responsibilities. Objective: This study aimed to examine the prevalence of and factors predicting menstrual irregularities among female students in Ho Chi Minh City, Vietnam. Methods: A cross-sectional study was conducted from April to July 2023 at the University of Medicine and Pharmacy at Ho Chi Minh City (UMP). Data were collected using self-administered questionnaires comprising sections on personal background, menstrual cycles, sleep duration, and academic stress. Descriptive statistics and multiple logistic regression were employed for data analysis. Results: Approximately 48.3% of participants experienced menstrual irregularities. Overweight or obese students were more likely to experience irregularities compared to those of normal weight (AOR = 7.56, 95% CI = 1.34, 80.8). Nursing majors (including nursing, midwifery, and anesthesia resuscitation nursing) showed a higher likelihood of irregularities compared to other majors (AOR = 2.5, 95% CI = 1.35, 4.13). Conclusion: This study highlights a significant prevalence of menstrual irregularities among female students. Interventions in nursing education should focus on promoting healthy lifestyles and regular physical activity to manage weight and mitigate menstrual irregularities.